Fast forward leadership / Louellen Essex and Mitchell Kusy. - Essex, Louellen (Financial Times Prentice Hall, 1999)
Developing the concept of the leadership exchange - exchanging a set of negative behaviours or precepts for a more positive, effective set - Fast Forward Leadership helps readers discover what they and their organistions must stop doing to succeed.